A study of masking level difference (MLD) in subjects with sensorineural hearing loss at various masker presentation levels - Ismail, Noraidah (Universiti Kebangsaan Malaysia, 1999)
Binaural masking level (BMLD) or simply MLD is one the behavioral tests which gained much attention due to its usefulness in differentiating amongst some types of hearing loss. Some studies showed that MLD can be used to distinguish between peripheral hearing loss and central auditory nervous system lesion at the brainstem level. The purpose of this study was to devise a clinical procedure for sensorineural hearing loss subjects using MLD. It was also to examine the difference between MLD value differences in normally hearing listeners and subjects with varying degrees of sensorineural hearing loss. Seventeen normally hearing, and 15 sensorineural hearing loss subjects were tested using two listening conditions (SoNo) and SπN). The results showed that there were significant differences between the MLD values in subjects with sensorineural hearing loss and those with normal hearing. The study suggested that the MLD values were affected by the presence of peripheral hearing loss, and is not always reliable in identifying brainstem lesion.